[18F]DPA‐C5yne, a novel fluorine‐18‐labelled analogue of DPA‐714: radiosynthesis and preliminary evaluation as a radiotracer for imaging neuroinflammation with PET. (24th April 2014) - Médran‐Navarrete, Vincent; Bernards, Nicholas; Kuhnast, Bertrand; Damont, Annelaure; Pottier, Géraldine; Peyronneau, Marie‐Anne; Kassiou, Michael; Marguet, Frank; Puech, Frédéric; Boisgard, Raphaël; Dollé, Frédéric
Abstract DPA‐C5yne, the lead compound of a novel series of DPA‐714 derivatives in which the fluoroethoxy chain linked to the phenylpyrazolopyrimidine scaffold has been replaced by a fluoroalkyn‐1‐yl moiety, is a high affinity (Ki: 0.35 nM) and selective ligand targeting the translocator protein 18 kDa. In the present work, DPA‐C5yne was labelled with no‐carrier‐added [18F]fluoride based on a one‐step tosyloxy‐for‐fluorine nucleophilic substitution reaction, purified by cartridge and HPLC, and formulated as an i.v. injectable solution using a TRACERLab FX N Pro synthesizer. Typically, 4.3–5.2 GBq of [18F]DPA‐C5yne, ready‐to‐use, chemically and radiochemically pure (> 95%), was obtained with specific radioactivities ranging from 55 to 110 GBq/µmol within 50–60 min, starting from a 30 GBq [18F]fluoride batch (14–17%). LogP and LogD of [18F]DPA‐C5yne were measured using the shake‐flask method and values of 2.39 and 2.51 were found, respectively. Autoradiography studies performed on slices of ((R, S)‐α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolopropionique (AMPA)‐lesioned rat brains showed a high target‐to‐background ratio (1.9 ± 0.3). Selectivity and specificity of the binding for the translocator protein was demonstrated using DPA‐C5yne (unlabelled), PK11195 and Flumazenil (central benzodiazepine receptor ligand) as competitors. Furthermore, DPA‐C5yne proved to be stable in plasma at 37°C for at least 90 min.